Long-term impact of pharmacist intervention in patients with bipolar disorder: extended follow-up to the EMDADER-TAB study (2020)
ABSTRACT: Background: Pharmaceutical care (PC) through the Dader method (DMet) vs. the usual care process (UCP) significantly reduced psychiatric hospitalizations and emergency service consultations during one year of followup of outpatients with bipolar I disorder (BD-I). To date, the effect of long-term PC on the use of health services by BD-I patients once pharmacist intervention has ended is unknown. Objective: To determine whether the effect of PC measured by the decrease in psychiatric hospitalizations and emergency service consultations is maintained one year after pharmacist intervention ceases. Methods: This was a retrospective analysis of patients who had previously participated in a randomized, controlled, prospective, single-center clinical trial to compare PC (intervention group) vs. UCP (control group) in BD-I patients. Data were collected from November 2012 to March 2014. The primary outcome was the use of health services measured by the number of psychiatric hospitalizations and emergency service consultations. Descriptive statistics, Student's t-test, Kaplan–Meier function, and Log-Rank test were used. Results: The study included 92 patients: 43 in the intervention group and 49 in the control group. Eleven psychiatric hospitalizations occurred for the intervention group and 19 for the control group. One year after pharmacist intervention ceased, there were no significant differences between the groups in psychiatric hospitalizations (p ¼ 0.261). There were 14 emergency service consultations for the intervention group, and 24 for the control group without significant differences (p ¼ 0.212). Conclusions: PC through the DMet has no long-term effects on psychiatric hospitalizations and emergency department consultations in patients with BD-I following discontinuation of pharmacist intervention; the effect dissipates when the intervention ceases. Future studies should focus efforts on identifying factors associated with PC that explain why the outcomes derived from this intervention are not maintained in the long term.